2021
DOI: 10.21203/rs.3.rs-815276/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Postoperative Pulmonary Infection in Elderly Patients With Hip Fracture: More Attention Needed

Abstract: Background: Postoperative pulmonary infection is a serious complication in elderly patients with hip fracture, it’s necessary to identify the influencing factors of pulmonary infection in patients with hip fracture.Methods: Elderly patients with hip fractures admitted from January 1, 2020 to July 31, 2021 were included. The characteristics of patients with pulmonary infection and no infection were evaluated and compared. Logistic multivariate regression analyses were conducted to assess the risk factors of pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…[49] Meanwhile, patients with a history of stroke, cancer, cardiovascular events, and cognitive function dysfunction can also significantly increase the incidence of HAP. [14,23,28,[31][32][33] Poole et al believed that patients with hip fractures combined with stroke had decreased living ability to varying degrees and were prone to dysphagia and HAP, which required early intervention for protection. [50] In a nationwide cohort study, Søgaard et al confirmed the correlation between cancer and HAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[49] Meanwhile, patients with a history of stroke, cancer, cardiovascular events, and cognitive function dysfunction can also significantly increase the incidence of HAP. [14,23,28,[31][32][33] Poole et al believed that patients with hip fractures combined with stroke had decreased living ability to varying degrees and were prone to dysphagia and HAP, which required early intervention for protection. [50] In a nationwide cohort study, Søgaard et al confirmed the correlation between cancer and HAP.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies [4,6,9,14,19,20,[23][24][25]29,[31][32][33][34] reported the relationship between chronic obstructive pulmonary disease (COPD) and HAP (Table 2). Among these, 3 studies (Bohl, Salarbaks, Ying) reported a negative association between COPD and HAP, while the remaining 11 studies identified COPD as a risk factor for HAP.…”
Section: Comorbidity -Copdmentioning
confidence: 99%
See 1 more Smart Citation